ANALISIS KEMISKINAN DIGITAL KABUPATEN/KOTA DI PROVINSI BANTEN DI MASA PANDEMI COVID-19 (JKPD Banten - Jurnal Kebijakan Pembangunan Daerah Provinsi Banten, 2022)
The Covid-19 pandemic that hit the world throughout 2020 has changed various aspects of life, especially in the use of Information and Communication Technology facilities due to changes in various human activities from offline to online. However, it turns out that there are still people who live with little or no access to technology (digitally poor). This study aims to calculate digital poverty according to Barrantes, its distribution and linkages to economic poverty in regencies/cities in Banten Province during the Covid-19 pandemic. The research method used is descriptive with data sourced from the BPS National Socioeconomic Survey in March 2020 and 2021. Data were analyzed using the digital poverty index and economic poverty index, as well as the GIS Quadrant. The results of the study show that in 2021 the digital poverty rate for districts/cities in Banten Province will generally decrease compared to the previous year. Two of the eight districts/cities in Banten have high digital poverty rates as well as high economic poverty rates, namely Pandeglang Regency and Lebak Regency. For this reason, the regional government of Banten province should be able to prioritize improvements to these two aspects in these two districts.
Keywords: Information and Computer Technology; digital poverti; economic poverty